Unsteady pressure motion of viscous - plastic fluid between two infinite planes - Thanh, Pham Hoai (Vietnam Journal of Mechanics, 1998)
In this paper we consider the problem on unsteady one - dimensional pressure flow of Svedov-Bingham's fluid between two infinite planes. We show that this problem can be solved completely by using Sliozkin-Targ's method with the approximation. We have some notices on the possibility of the application of this method for solving a class on unsteady flow of viscous-plastic fluid in pipelines without any supplementary assumption.